2021
DOI: 10.31234/osf.io/6vh37
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the influence of emotional expressions on perceptual sensitivity to faces overcoming interocular suppression

Abstract: Understanding faces and their emotional expressions is essential for social interaction. Past studies have prompted suggestions that some facial features may be processed unconsciously. Evidence for such unconscious processing has predominantly come from the Breaking Continuous Flash Suppression (b-CFS) paradigm, which measures the time it takes different stimuli to overcome interocular suppression. For instance, it has been claimed that suppressed fearful expressions are detected faster that neutral expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…More recently, Kobylka et al [58] showed that the FIE can be found both when using localisation (left/right) and stimulus categorisation (face/house) bCFS tasks. Similarly, Lanfranco et al [61,62] and Stein & Peelen [63] replicated the FIE by showing participants CFS-suppressed faces for predefined exposure durations; in these studies, the FIE was replicated by measuring both sensitivity to face location (left/right) and stimulus categorisation (face inversion, emotion, or gaze direction; however, note that it has been suggested that the FIE may be noisy or weak when using CFS [62,64]). They found that at specific exposure durations sensitivity to suppressed upright faces was significantly higher than to suppressed inverted faces, thus indicating that the FIE arises from differences in perceptual sensitivity.…”
Section: Facial Configuration and The Face-inversion Effectmentioning
confidence: 90%
See 3 more Smart Citations
“…More recently, Kobylka et al [58] showed that the FIE can be found both when using localisation (left/right) and stimulus categorisation (face/house) bCFS tasks. Similarly, Lanfranco et al [61,62] and Stein & Peelen [63] replicated the FIE by showing participants CFS-suppressed faces for predefined exposure durations; in these studies, the FIE was replicated by measuring both sensitivity to face location (left/right) and stimulus categorisation (face inversion, emotion, or gaze direction; however, note that it has been suggested that the FIE may be noisy or weak when using CFS [62,64]). They found that at specific exposure durations sensitivity to suppressed upright faces was significantly higher than to suppressed inverted faces, thus indicating that the FIE arises from differences in perceptual sensitivity.…”
Section: Facial Configuration and The Face-inversion Effectmentioning
confidence: 90%
“…Many studies have employed CFS to replicate the FIE [24,[56][57][58][59][60][61][62][63]], which appears to be stronger for faces than for other objects [63]. Zhou Fig.…”
Section: Facial Configuration and The Face-inversion Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested a processing advantage and faster access to awareness for upright over inverted faces [15][16][17][18][19][20] , and for emotional over neutral faces 21,22 . (Although the latter claim, in particular, has been challenged [23][24][25][26] ). If so, processing -and possibly awareness -of upright and emotional faces should require shorter minimal exposures than inverted and neutral faces, respectively.…”
Section: Introductionmentioning
confidence: 99%